Contextualizing Learning for Rural Community using Library-in-a-Box : Experience from Penan Community - Narayanan, Kulathuramaiyer; Amit, Pariyar; Johari, Abdullah; Chuah, Kee Man (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Online Learning Platforms (OLP) have incredible potential to achieve the vision stated in the Malaysia Education Blueprint (2015-2025) - to become a nation of lifelong learners and to embrace globalized online learning. But there exists technological and social challenges in replicating the connectivity model of OLP to achieve the much extended and inclusive vision of connecting the rural population to the knowledge ecosystem. In response, the Institute of Social Informatics and Technological Innovations (ISITI) has developed a low-cost offline learning tool ‘Library-in-a-Box’. This research investigates the suitability of offline learning platform/tool to meet the knowledge demands of remote and indigenous Penan communities from the Borneo Malaysia. Based on community based participatory action research, we conducted learning session and interview with the community. The findings revealed enablers and inhibitors – both anticipated when contextualizing offline learning to rural community. The enablers of offline learning are delivery of value-added content, affordability and connectivity, fostering communal values, proper utilization of local resources, early childhood development and empowerment of local capacities especially teachers. While the inhibitors are dispute over control and ownership of content/tool, quality issues of content, detrimental effects on health and social well-being, threat to culture and undervaluing teacher’s role. This research reaffirmed technology as a partial solution and suggested offline learning modus operandi to reflect the socio-cultural context.